Amino−Organolithium Compounds and their Aggregation for the Synthesis of Amino−Organoaluminium Compounds. Issue 23 (13th May 2021) - Bodach, Alexander; Ortmeyer, Jochen; Herrmann, Bastian; Felderhoff, Michael
Abstract: Here, we present a thorough structural study of small, easily accessible amino−organolithium compounds with bridging phenyl and naphthyl moieties. Their crystal structures most likely represent their aggregation as tetramers and dimers in both hydrocarbon and ethereal solvents. These amino−organolithium compounds were further used to generate their corresponding aluminium compounds as a model system. Their crystal structures are reported too. All structures are discussed with a focus on the different steric demands and bridging moieties. Additionally, the crystal structures of neophyllithium and decomposition products of some of the compounds mentioned above are reported. This study provides additional data for the future design and synthesis of amine stabilised organolithium and ‐aluminium compounds. Abstract : A structural study of amino−organolithium compounds is presented with an emphasis on their aggregation as tetramers and dimers. These compounds were further used to generate their corresponding aluminium compounds whose crystal structures as well as those of neophyllithium and decomposition products are reported too. This study provides additional data for the future design and synthesis of amino−organolithium and ‐aluminium compounds.